Early development of the chondrocranium in Chrysichthys auratus. - CHIKOU, ANTOINE; Vandewalle, Pierre; LALEYE, PHILIPPE A.; Paramentier, Eric; Huriaux, F; Focant, B. (My University, 1999)
The inception and development of the cartilaginous cephalis skeleton of Chrysichthys auratus is described from hatching to about 18 days post-hatching. At hatching, no skeletal structure is present. Not until day 3 do clearly delimited cranial primordia become apparent. As in many siluriforms, the neurocranium is platybasic from the start, the suspensorium constitutes, with Meckel's cartilage and the hyoid bar, a single cartilaginous element, and the junction between the front and rear of the neurocranium is complete on day 4. By day 8 the quadratomandibular joint has formed and the tectum posterius has appeared. Cartilage reduction first affects the trabecular bars, then, markedly, the visceral arches. By day 18 the braincase floor has almost disappeared.
Keywords: Early development the chondrocranium Chrysichthys auratus